2007
DOI: 10.1111/j.1752-1688.2007.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Parent and Metabolite Fate and Transport in Subsurface Drained Fields With Directly Connected Macropores1

Abstract: Few studies exist that evaluate or apply pesticide transport models based on measured parent and metabolite concentrations in fields with subsurface drainage. Furthermore, recent research suggests pesticide transport through exceedingly efficient direct connections, which occur when macropores are hydrologically connected to subsurface drains, but this connectivity has been simulated at only one field site in Allen County, Indiana. This research evaluates the Root Zone Water Quality Model (RZWQM) in simulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…In general, the numerical simulations suggested an even greater contributing area with directly connected macropores than suggested by Akay and Fox (2007) and Fox et al (2004) The need for calibration observed by Fox et al (2007) is supported by these numerical simulations that show that the contributing area depends on the site‐specific macropore depth of penetration.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…In general, the numerical simulations suggested an even greater contributing area with directly connected macropores than suggested by Akay and Fox (2007) and Fox et al (2004) The need for calibration observed by Fox et al (2007) is supported by these numerical simulations that show that the contributing area depends on the site‐specific macropore depth of penetration.…”
Section: Resultsmentioning
confidence: 61%
“…C oncerns exist about the rapid transport of contaminants, such as pesticides (Fox et al, 2004), pathogens (Joy et al, 1998; Geohring et al, 1999; Jamieson et al, 2002; Shipitalo and Gibbs, 2005), and nutrients from the soil surface to groundwater through macropores (Magesan et al, 1995; Kladivko et al, 1999; Shipitalo and Gibbs, 2000). Commonly observed short‐circuiting in many subsurface drainage field studies has been hypothesized to be due to direct hydrologic connectivity between macropores and subsurface drains (Fox et al, 2004, 2007; Shipitalo and Gibbs, 2000, 2005). Directly connected macropores can result in the rapid transport of contaminants from the soil surface into the subsurface drains and then into adjacent receiving streams and channels, bypassing the soil's filtering capacity.…”
mentioning
confidence: 99%
“…Also, the empirical model was evaluated against measured Δ P using linear regression and also based on the STDD: STDD=i=1n(normalxmnormalxp)2nwhere x m and x p are the i th observed and predicted values of n observations, respectively. This function has been used in the past for quantitative evaluation of pesticide fate and transport models (Pennell et al, 1990; Fox et al, 2004; Fox et al, 2006; Fox et al, 2007). This research used a criterion that the STDD between measured and predicted Δ P should be less than 15%.…”
Section: Methodsmentioning
confidence: 99%
“…The Root Zone Water Quality Model (RZWQM) incorporates these elements and has been successfully tested and used to simulate pesticide and pesticide metabolite fate and transport in numerous field and laboratory studies . Furthermore, the RZWQM has recently been used for accurate simulation of metolachlor and OXA fate in widely different soil and climatic conditions in Maryland and Nebraska .…”
Section: Introductionmentioning
confidence: 99%